2021
DOI: 10.1177/0958305x211029636
|View full text |Cite
|
Sign up to set email alerts
|

Do remittance and renewable energy affect CO2 emissions? An empirical evidence from selected G-20 countries

Abstract: The study aims to compare CO2 emissions, renewable energy, trade openness, gross domestic product (GDP), financial development (FD), and remittance in selected G-20 countries. The study carried out fully modified ordinary least square (FMOLS) and dynamic ordinary least square (DOLS) models for estimation covering annual data from the year 1990–2019. LM tests detected the cross-section dependency while stationarity of the variables was checked through Levin-Lin-Chu and Im-Pesaran-Shin tests along with Hansen's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 37 publications
4
26
1
Order By: Relevance
“…Operators of social networks must identify the reason propelling continued use of social network sites, alongside attracting more users. Nevertheless, previous studies on information systems in the last two decades have mainly concentrated on behavior–cognition approaches, for instance, the technology acceptance model (TAM), theory of planned behavior (TPB), and theory of reasoned action (TRA) with their variants ( Tarsakoo and Charoensukmongkol, 2020 ; Jamil et al, 2021b ). According to Ismail et al (2018) , perceived use and satisfaction positively impact a user’s continuance intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Operators of social networks must identify the reason propelling continued use of social network sites, alongside attracting more users. Nevertheless, previous studies on information systems in the last two decades have mainly concentrated on behavior–cognition approaches, for instance, the technology acceptance model (TAM), theory of planned behavior (TPB), and theory of reasoned action (TRA) with their variants ( Tarsakoo and Charoensukmongkol, 2020 ; Jamil et al, 2021b ). According to Ismail et al (2018) , perceived use and satisfaction positively impact a user’s continuance intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, employees who have built up social capital can better identify and negotiate administrative support services, such as organizational work-life balance programs, feel more comfortable accessing these services, and obtaining supervisor support. In a recent study, researchers found that some employees are hesitant to use organizational support services and that employee use of family friendly corporate resources can be influenced by the quality of employee-manager relations (Jamil et al, 2021b). Workers with a greater degree of link embeddedness had an easier time implementing current ameliorative measures, resulting in a reduction in the experience of stress resulting from work and family conflict compared to employees with a lower level of link embeddedness.…”
Section: The Moderating Effect Of On-the-job Link Embeddednessmentioning
confidence: 99%
“…Loyalty products and services mark a differentiation from other providers and thus also add value. Customers play an important and efficient role in developing innovative manufacturing systems, which led to the development of the lean manufacturing concept (Jamil et al, 2021b ). Good customer relationships lead to the importance of the dissemination of environmental and social manufacturing practices that can improve social and ecological performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Carbon dioxide is a greenhouse gas, which contributes to climate change and is a worldwide issue. Reducing the amount of carbon dioxide released into the atmosphere is one way to combat global warming and pollution (Jamil et al, 2021b ). As a consequence of reducing waste, lean manufacturing may assist in reducing pollution since it reduces cycle times and increases resource utilization.…”
Section: Literature Reviewmentioning
confidence: 99%